Pengaruh Penambahan Variasi Abu Janggel Jagung Dengan Serat Bambu Terhadap Uji Kuat Tarik Belah - Kahfi Almachzuuni; Warsito Warsito; Eko Noerhayati (Universitas Islam Malang, 2020)
Concrete is a material that generally becomes the community's need for construction infrastructure facilities, the composition of which includes cement mixture, coarse aggregate, fine aggregate, water, and or without other added ingredients. Pozzolan is an added material derived from nature or rock, which consists mainly of reactive silica and alumina elements. Corn clover ash has a high silica content of 29.7% so that it can be a partial substitution of cement. Bamboo can be a substitute material because it has a relatively cheap price, is easily available, is natural, and has a tensile strength of 4170 kg / cm2. This study uses corn clover as a partial substitution of cement and bamboo fiber with a length of 5 cm and a diameter of 1 cm as a partial substitution of coarse aggregate. With variations in the percentage of ash and fiber substitution are 0: 0%, 0: 5%, 0: 10%, 5: 0%, 5: 5%, 5: 10%, 10: 0%, 10: 5%, and 10 : 10%. Concrete tensile strength test performed on concrete specimens aged 14, 21, and 28 days. Concrete tensile strength test results 28 days for normal concrete obtained fct= 29.0 MPa. The percentage increase of 5% corn beard ash and 5% bamboo fiber produced concrete specimens with the highest tensile strength values than normal concrete, namely fct= 32.1 MPa. Regression analysis results obtained R2= 0.603 which means that the influence of mixing of corn clover and bamboo fiber on the tensile strength of concrete is 60.3%. Keywords: Concrete tensile strength, corn clover ash, bamboo fiber.